PENGEMBANGAN GAME EDUKASI MENGGUNAKAN SOFTWARE RPG MAKER VX ACE PADA MATERI HUKUM ARCHIMEDES - Hendri Prasetio; Chandra Ertikanto; Agus Suyatna (Jurnal Pembelajaran Fisika, 2016)
The purposes of this development research were to produce educational game that can be used for playing while learning about archimedes law materials through the game on PC and determine the effectiveness of educational games. The steps of Education game used development procedure based on Sadiman et. al.procedures, which included the need analysis, formulating the purpose, formulating the items of the materials, compiling the evaluation instrument, writing script of media, the first product, validation by the expert, test of the product, and the final product. Experimental results showed that the products developed got score 3.20 on attractiveness,3.44 on easiness and 3.58 on usefullness, meanwhile the aspect was very easy to use and the game content can be clearly understood and effectively used as a supplement or media for playing while learning that students were completed the minimum completeness criteria that reached 78.13%.Tujuan penelitian pengembangan ini adalah menghasilkan game edukasi yang dapat digunakan untuk bermain sambil belajar mengenai materi hukum archimedes melalui permainan pada PC dan mengetahui keefektifan game edukasi. Tahapan pengembangan game edukasi menggunakan prosedur pengembangan menurut Sadiman, dkk. meliputi analisis kebutuhan, merumuskan tujuan, merumuskan butir-butir materi, menyusun instrumen evaluasi, menulis naskah media, produk awal, validasi ahli, uji coba lapangan, dan produk akhir. Hasil uji coba menunjukkan bahwa produk yang dikembangkan memperoleh nilai kemenarikan 3,20,kemudahan 3,44 dan kemanfaatan 3,58 sedangkan dalam aspek penggunaan sangat mudah dalam pengoprasian dan isi game dapat dipahami dengan jelas serta efektif digunakan sebagai suplemen atau media untuk bermain sambil belajar yaitu siswa tuntas dari Kriteria Ketuntasan Minimal mencapai 78,13%.Kata kunci:game edukasi, hukum archimedes, pengembangan